Adsorption Removal of Rhodamine-B Dye from Aqueous Solution Using Rhamnus Stone as Low Cost Adsorbent - Al-Rudaini, Khudhair A (Al-Nahrain Journal of Science, 2017)
In this study, low-cost Rhamnus stone was used as adsorbents for the adsorption of RhodamineB (RhB) dye from aqueous solution by batch experiments under different condition of adsorbent weight, contact time, pH and initial dye concentration. Kinetic data obeyed to Ho-Mckay pseudo second order equation. Freundlich and Langmuir isotherms were used to test the equilibrium data and the results shows better fit with Langmuir isotherm with maximum adsorption capacity 39mg/g. Thermodynamic parameters show the adsorption of RhB onto Rhamnus stone was spontaneous and endothermic.